THE USE OF PSYCHOLOGICAL TRAINING IN THE DEVELOPMENT OF COOPERATION SKILLS IN YOUNG CHILDREN (American Journal of Interdisciplinary Research and Development, 2026)
This article examines the theoretical foundations of the development of cooperation, the concept of skill, and its importance in the social, educational, and professional environment. The role of cooperation in improving interpersonal relations, increasing organizational efficiency and ensuring the sustainable development of society is analyzed, cognitive, practical and social aspects of skills are characterized, and their role in personal development and professional development is determined. In addition, modern methods and mechanisms for the formation of a culture of cooperation are proposed, psychological and pedagogical mechanisms for the formation of skills are differentiated. The article also examines the effectiveness of psychological training in developing cooperation skills in young children. The article analyzes the structure of cooperation skills, psychological characteristics of adolescence and the content of training work. In addition, the influence of group training on interpersonal relationships, the formation of mutual trust and responsibility is characterized.